Locating residential on-street electric vehicle charging infrastructure: A practical methodology. (September 2019) - Grote, Matt; Preston, John; Cherrett, Tom; Tuck, Neil
Highlights: Virtually all owners of Electric Vehicles (EVs) prefer charging at home overnight. A lack of off-street parking for home charging restricts EV uptake. Local Government can provide on-street residential charge points as alternatives. A simple method for identifying charge point installation locations was developed. The method was applied successfully to a case study urban area of Southampton, UK. Abstract: Depending on the method of electricity generation, mass-market penetration of electric vehicles has the potential to reduce emissions of greenhouse gases and air pollutants considerably, and to reduce dependency on fossil fuels. This paper presents a novel methodology for Local Government Authorities (LGAs) to identify suitable locations for the initial provision of residential on-street Plug-in Electric Vehicle (PEV) charging infrastructure in urban areas to help remove barriers to PEV uptake. The methodology is practical for use by LGAs with limited financial resources as it is based on simple Geographic Information System (GIS) analysis of routinely available census and parking data to identify the spatial overlaps between areas where residents are most likely to be PEV users and areas where there is a high reliance on residential on-street parking. The methodology has been implemented in practice to determine a charging infrastructure installation strategy for Southampton, UK, where 128 streets (out of 1924 in total) were recommended as suitable locations. These streets were reviewed by a group of experts during a workshop and confirmed as suitable locations for the initial installation of residential on-street charge points in the city.